A disfunção ventricular direita pós-infarto do miocárdio está associada com o desenvolvimento da insuficiência cardíaca - Fernandes, Aurélia Araújo (2010)
Heart failure (HF) is the major cause of death and morbidity after myocardial infarction (MI) that can result in reduced cardiac output, increased venous pressure and cardiac remodeling. Usually, the left ventricle failing causes right dysfunction being related to greater risk of hospitalization. It has been suggested that assessment of right ventricle (RV) function is of important value to prognostic of HF after MI. Therefore, the aim of this study was to assess right ventricle contractility early (one week) and late phase (eight weeks) after MI. MI with signal of HF (HF group) and without signal of HF (Inf group) were compared to a sham-operated group (sham). Wistar male rats were anaesthetized with Ketamine (50 mg/kg) and Xylazine (5 mg/kg), i.m., and MI was induced through left coronary artery ligation at 3 mm of its origin. After 1 and 8 weeks the rats was anaesthetized with urethane (1.2 g/kg i.p.) and a catheter was inserted into the aorta and left ventricle to pressures measurements using a pressure transducer (TSD 104A) coupled to a Biopac MP100 system. Strips from the right ventricle were removed and attached to an isometric transducer and superfused at 30ºC with Krebs solution, stimulated at 0.5 Hz and 80 mV. The experimental protocols were approved by the local animal ethics committee (CEUA-EMESCAM). Both infarct groups presented same scar size (Inf 1 week= 32.4 ± 3; HF 1 week=33.7 ± 2.2; Inf 8 weeks= 26.5 ± 1.1; HF 8 weeks= 25 ± 0.9). The scar size did not have correlation with HF signals (left ventricle end diastolic pressure (LVEDP), increased lung weight and body weight ratio (LW/BW) and right ventricle to body weight ratio (RV/BW) neither with RV contractility. The LVEDP increased in HF group but not in the Inf group early (1 week: HF=15 ± 1*; Inf=5.2 ± 0.8; Sham=3,7 ± 0,6 mmHg) and late after MI (8 weeks: Hf=16 ± 2.5*, Inf- 7.5 ± 0.7; Sham= 5.2 ± 0.8 mmHg), *P< 0.05 ANOVA one way, post hoc Tukey. In the HF group LW/BW and RV/BW ratio was increased in the late phase, but not in the early phase after MI. The body weight was smaller in the HF group at 1 week, but similar to sham 13 and Inf 8 weeks after MI. Therefore, there was a negative correlation between force development in the RV strips and body weight in both early and late phase after MI. The inotropic responses to Ca2+ and Isoproterenol were preserved in HF group one week after MI and reduced at 8 weeks (8 weeks; CaCl2 2.5 mM: sham= 157 ± 18.4; Inf= 138 ± 17.3; HF= 62 ± 10.3 g/g P<0.05; Isoproterenol 10- 5 M: sham = 149 ± 14; Inf = 137 ± 18.7; HF = 58 ± 8.1 g/g P<0.05). Inversely, in the Inf group, the positive intropic response was reduced in the early phase and reduced in the late phase (1 week; CaCl2 2.5 mM: Sham= 186 ± 8.3; Inf = 135 ± 11.7; HF= 158 ± 13.1 g/g; P<0.05; Isoproterenol 10-5 M: Sham= 145 ± 9.9; Inf= 108 ± 10.8; HF= 166 ± 12 g/g P<0.05). The Ca2+ handling proteins expression (sarcoplasmatic reticulum calcium pump (SERCA-2a), phosfolamban (PLB total), PLB phosphorylated and Na+ /Ca2+ exchange) were not different among the groups in the early phase. But, in the late phase there was a SERCA-2a overexpression and an higher SERCA/PLB ratio just in the Inf group. In conclusion, the scar size did not correlate with HF signals neither with RV contractility. The RV dysfunction was found in the late phase after MI in rats with HF. However, the rats with HF maintain the RV function in early phase after MI. The infarct rats without HF maintained the RV contractility and increase SERCA-2a expression in the late phase after MI. The different inotropic βadrenergic response between the groups with and without HF could be induced by different mechanisms involving upregulation and downregulation of the βreceptors during the early and late phase after MI.